The health gap and HRQoL inequalities in Greece before and during the economic crisis - Yfantopoulos, John; Chantzaras, Athanasios; Yfantopoulos, Platon (Frontiers in Public Health, 2023)
The aim of this study was twofold: i) to assess the health gap among young socio-economic groups generated by the economic crisis in Greece and ii) to investigate HRQoL (Health Related Quality of Life) inequalities using the Theil index. Methods The EQ-5D-5L instrument was administered to a sample of 4177 young individuals in Greece, mean age of 22.3 (±SD 4.8) and 53.8% males, and 46.2% females. The EQ-5D-5L instrument was used to collect data. Subjects were asked to assess their HRQoL during the economic crisis of 2016 and to recall it before the crisis of 2009. The health gap was assessed on EQ-VAS, the EQ-5D-5L Index, and the five dimensions of the EQ-5D-5L. Regression analysis examined the effects of the economic crisis on age, sex, education, and income on the EQ-VAS and EQ-5D-5L. The Theil index assessed HRQoL inequalities. Results The economic crisis deteriorated the HRQoL of young Greeks. The EQ-VAS was reduced during the crisis by -10.05%. (p<0.001) and the EQ-5D-5L index declined by -19.61% (p<0.001). The prevalence of the health gap has also deteriorated: Mobility (change by 66.8% (p<0.001)), Self-care (change by 61.0% (p<0.001)), Usual activities (change by 97.1% (p<0.001)), Pain/discomfort (change by 65.0% (p<0.001), and Anxiety/depression (change by 70.5% (p<0.001). Reductions in EQ-5D-5L indices were associated with great inequalities in the distribution of health among age, gender, income, and educational groups. The EQ-5D-5L health gap among the poor was greater (0.198), in comparison to the rich (0.128). The EQ-5D-5L health gap in primary education was 0.211, and for tertiary education, was 0.16. The Theil index indicated an increase in income-related HRQoL inequalities by 222.3% for the EQ-5D-5L index and by 124.2%. for the EQ-VAS. The effects of demographic and socioeconomic variables on the EQ-VAS were found statistically significant: sex (p<0.05), age (p<0.001), education (p<0.001), and income (p<0.001). Conclusions The EQ-5D-5L instrument is a powerful tool for assessing the health gap and the HRQoL inequalities among young people in Greece. The findings indicate the importance of developing effective health policies to combat inequalities and mitigate the impact of austerity measures on the quality of life of the young.